Neurodegenerative Diseases: The Effect of Omega-3 Fatty Acids on Neuroinflammation - R, Priyadharshini; S, Sreelakshmi; S.B, Tanuvarthini; S, Aishwarya; V, Hema; Xavier, Milagrin (Indian Journal of Pharmacy Practice)
Omega-3 fatty acids’ anti-inflammatory qualities and impact on the integrity of neuronal membranes make them promising for the treatment of neurodegenerative diseases including Parkinson’s and Alzheimer’s. Omega-3 and omega-6 Polyunsaturated Fatty Acids (PUFAs) influence neuroinflammation and cognitive function, making them essential for brain health. Neurodegeneration and mental disorders are associated with deficiency in omega-3 polyunsaturated fats. According to clinical research, taking omega-3 supplements-especially those containing DHA and EPA-may help with cognitive performance and lower neuroinflammation in people with Parkinson’s and Alzheimer’s illnesses. Mechanistically, omega-3 PUFAs control inflammatory pathways and synaptic function, while DHA suppresses tau protein phosphorylation and Aβ buildup. Omega-3 PUFAs can be obtained through diet, such as fatty fish, although supplementation may be required, particularly in populations with limited consumption or conversion capacity. One useful application of omega-3 fatty acid fortification is providing easy methods to integrate it in everyday diets. Overall, study is needed to determine whether omega-3 fatty acids can prevent or treat neurodegenerative diseases.
Keywords: Omega-3 Fatty Acids; Neuro Degenerative Disorder; Docosahexaenoic Acid; Elcosapentaenoic Acid